Molecular methods for the verification of bacterial decontamination - Willoughby, Sarah L. (2021)
The UK faces a continuing threat from the terrorist use of Chemical, Biological, Radiological and Nuclear (CBRN) materials. As such, it maintains and extensive counter-CBRN research programme. The nature of biological threat agents necessitates their handling in highly secure microbiological containment facilities. Therefore safe surrogates, which mimic their key characteristics, are used to assess their likely impact in real-world scenarios. To further develop the tools available for use with surrogates, this work provided unfinished genome sequence data for two important bacteria, E. coli MRE162 and B. atrophaeus (or BG) and used it to design novel real-time PCR assays for their detection. The E. coli PCR assay was converted and optimised for use with propidium monoazide (PMA), providing a novel viability assay for the absolute quantification of live and VBNC E. coli. The E. coli sequence data was further used in mapping transcriptome data that was generated for decontaminant-treated and untreated E. coli MRE162. The aim being to identify genes expressing during decontamination stress, which should represent ideal candidates for the design of mRNA-based viability assays for the detection of the surrogate following incomplete decontamination. The adoption of B. thuringiensis HD-1 Cry- as the surrogate of choice in UK Defence research necessitated the design of further real-time PCR assays, again with the aim of conversion to viability assays. Work towards identifying suitable conditions to generate samples of decontaminant stressed B. thuringiensis HD-1 Cry- for transcriptome sequencing was also undertaken.